2019
DOI: 10.1002/alr.22339
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal IgE, IgG4, and mucosal eosinophilia in individuals with dysphagia

Abstract: Background Eosinophilic esophagitis (EoE) is an inflammatory disease of the esophagus, producing failure to thrive in infants and dysphagia with food impaction in older children and adults. Although most people with EoE manifest atopic/allergic disease, the specific allergens to which immunoglobulin E (IgE) is directed, if any, have not yet been characterized. Methods Mucosal brush biopsy (MBB) and solid tissue biopsy (STB) specimens were prospectively obtained from 25 individuals with dysphagia and suspicion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…For example, Clayton et al identified increased levels of total Immunoglobulin G4 in tissue homogenates from EoE, suggesting that local immune responses occur 18 . Forceps and brush biopsies have revealed that immunoglobulins (Immunoglobulin G4 and Immunoglobulin E) are increased in EoE tissues 21 . Although not studied specifically in EoE, Immunoglobulin A is a known mucosal exclusion antibody secreted on the gastrointestinal surface to protect the body from potential threats, such as bacteria and viruses 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clayton et al identified increased levels of total Immunoglobulin G4 in tissue homogenates from EoE, suggesting that local immune responses occur 18 . Forceps and brush biopsies have revealed that immunoglobulins (Immunoglobulin G4 and Immunoglobulin E) are increased in EoE tissues 21 . Although not studied specifically in EoE, Immunoglobulin A is a known mucosal exclusion antibody secreted on the gastrointestinal surface to protect the body from potential threats, such as bacteria and viruses 22 .…”
Section: Introductionmentioning
confidence: 99%
“…One study looking at the efficacy of an antibody against IgE (omalizumab) compared with placebo over 16 weeks147 did not find any benefit, but histological analysis of the oesophageal biopsies showed an increase in IgG-4 in the lamina propria of patients with EoE compared with controls; however the role of IgG-4 in the pathogenesis of EoE remains uncertain. Food-specific IgE/IgG antibodies have been detected in oesophageal samples but the relevance to underlying pathophysiology and management of EoE is unclear 148 149. Targeted dietary elimination on the basis of IgE testing is no more effective than empirical dietary elimination 123 150.…”
Section: Managementmentioning
confidence: 99%
“…However, other studies collecting IgG4 directly from the esophageal mucosa showed no differences in the levels of food-specific IgG4 between patients and controls ( Ramaswamy et al, 2019 ) and studies evaluating the efficacy of serum or mucosal IgE or IgG-directed tests in the identification of causal food allergens yielded disappointing results.…”
Section: Focus On Type 2 Inflammation: the Protagonistsmentioning
confidence: 99%